The knowns and unknowns of phosphorus loading into grains, and implications for phosphorus efficiency in cropping systems. (8th December 2015) - Wang, Fanmiao; Rose, Terry; Jeong, Kwanho; Kretzschmar, Tobias; Wissuwa, Matthias
Highlight: We point out the main knowledge gaps related to the regulation of seed phosphorous loading and suggest that capping seed phosphorous loading will enhance the efficiency of phosphorous utilization in agriculture. Abstract: Inefficient use of phosphorus (P) in agriculture adds to production costs, increases the risk of eutrophication of waterways, and contributes to the rapid depletion of the world's non-renewable rock phosphate supplies. The removal of large quantities of P from fields in harvested grains is a major driver in the global P cycle, but opportunities exist to reduce the amount of P in harvested grains through plant breeding. Using rice ( Oryza sativa L.) as a model crop, we examine our current understanding of the process of P loading into grain and its regulation by genetic and environmental factors. We expose a dearth of knowledge on the physiological processes involved in loading P into grains, poor resolution of the genes and networks involved in P mobilization from vegetative tissues to grains, and limited understanding of genetic versus environmental contributions to variation in grain P concentrations observed among genotypes. We discuss potential breeding strategies and highlight key research gaps that should be addressed to facilitate these breeding approaches. Given the strong economic and environmental incentives for a low grain P trait, we suggest that some of the investment and resources currently directed to determining the molecular regulation of P starvation responses in model plant species should be diverted to resolving the physiology, genetics, and molecular regulation of P loading into cereal grains.